Optimization of Government Policies in Guaranteeing Women's and Children's Rights: An Analysis of Legal Effectiveness Theory and Maqāṣid al-Sharī’ah - Azizah Khairiyah; Ahmad Fauzi (UIN Siber Syekh Nurjati Cirebon, 2026)
This study examines the gap between comprehensive regulations for protecting women and children in Indonesia and their limited effectiveness in practice. Although legal frameworks are well established, their implementation remains inconsistent. Previous studies have largely emphasized normative or theological dimensions, resulting in limited integration of legal effectiveness with ethical principles derived from Maqāṣid al-Syarī’ah. This research aims to evaluate government policy implementation by combining Legal Effectiveness Theory with Maqāṣid al-Syarī’ah to assess both regulatory performance and ethical orientation. This research employs a qualitative method and a normative juridical approach, supported by a literature review. Data were collected from legislation, academic works, and relevant prior studies. The analysis applies descriptive, analytical, and comparative techniques to identify discrepancies between legal provisions and their application. The findings reveal that implementation remains suboptimal despite the availability of comprehensive regulations. Weak coordination among institutions is the primary constraint, accompanied by limited resources, inadequate facilities, and low public awareness of legal rights. In addition, persistent patriarchal norms continue to influence policy outcomes and hinder protection efforts. In conclusion, improving policy effectiveness requires an integrative approach that connects legal structure, social conditions, and ethical values. The incorporation of Maqāṣid al-Syarī’ah, particularly in safeguarding life, intellect, lineage, and dignity, strengthens the moral direction of public policy. This study contributes to the development of a more coherent and equitable framework for protecting women and children in Indonesia. Keywords: Legal Effectiveness; Women and Children; Maqāṣid Al-Syarī’ah; Public Policy; Legal Protection